Neuromyelitis optica: evaluation of 871 attacks and 1,153 treatment courses - Kleiter, Ingo Wolfram; Gahlen, Anna; Borisow, Nadja; Fischer, Katrin; Wernecke, Klaus-Dieter; Wegner, Brigitte; Hellwig, Kerstin; Pache, Florence; Ruprecht, Klemens; Havla, Joachim; Krumbholz, Markus; Kümpfel, Tania; et al. (Annals of neurology, 2016)
Objective Neuromyelitis optica (NMO) attacks often are severe, are difficult to treat, and leave residual deficits. Here, we analyzed the frequency, sequence, and efficacy of therapies used for NMO attacks. Methods A retrospective review was made of patient records to assess demographic/diagnostic data, attack characteristics, therapies, and the short-term remission status (complete remission [CR], partial remission [PR], no remission [NR]). Inclusion criteria were NMO according to Wingerchuk's 2006 criteria or aquaporin-4 antibody-positive NMO spectrum disorder (NMOSD). Remission status was analyzed with generalized estimating equations (GEEs), a patient-based statistical approach. Results A total of 871 attacks in 185 patients (142 NMO/43 NMOSD, 82% female) were analyzed. The 1,153 treatment courses comprised high-dose intravenous steroids (HD-S; n = 810), plasma exchange (PE; n = 192), immunoadsorption (IA; n = 38), other (n = 80), and unknown (n = 33) therapies. The first treatment course led to CR in 19.1%, PR in 64.5%, and NR in 16.4% of attacks. Second, third, fourth, and fifth treatment courses were given in 28.2%, 7.1%, 1.4%, and 0.5% of attacks, respectively. This escalation of attack therapy significantly improved outcome (p < 0.001, Bowker test). Remission rates were higher for isolated optic neuritis versus isolated myelitis (p < 0.001), and for unilateral versus bilateral optic neuritis (p = 0.020). Isolated myelitis responded better to PE/IA than to HD-S as first treatment course (p = 0.037). Predictors of CR in multivariate GEE analysis were age (odds ratio [OR] = 0.97, p = 0.011), presence of myelitis (OR = 0.38, p = 0.002), CR from previous attack (OR = 6.85, p < 0.001), and first-line PE/IA versus HD-S (OR = 4.38, p = 0.006). Interpretation Particularly myelitis and bilateral optic neuritis have poor remission rates. Escalation of attack therapy improves outcome. PE/IA may increase recovery in isolated myelitis. Ann Neurol 2016;79:206-216
First published: 04 November 2015
Gesehen am 13.05.2020